2007
DOI: 10.1007/bf02849962
|View full text |Cite
|
Sign up to set email alerts
|

First aid: Level of knowledge of relatives and bystanders in emergency situations

Abstract: Bystanders who are able to provide immediate first aid to patients who require emergency care can make a big difference in the outcome. Thus, first-aid training should be made available to as many people as possible. The aims of this study were to assess the level of first-aid knowledge among bystanders in emergency situations and to identify factors that affected this level of knowledge. At Dokuz Eylul University Emergency Service between February 1 and February 15, 2002, 318 bystanders were given a questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
1
22
1
Order By: Relevance
“…Eldosoky (2012) showed that young mothers, employed mothers, educated mothers (with university degrees) and mothers with high socio-economic status had higher knowledge and more positive attitudes compared to others. In addition, Tomruk et al showed that studying at university results in an increase in mothers' knowledge about home injuries (Tomruk, Soysal, Gunay, & Cimrin, 2007). Thein et al (2005) emphasised the low level of mothers' knowledge about home safety and prevention of home accidents and showed that an increase in educational status results in an increase in mothers' knowledge.…”
Section: Discussionmentioning
confidence: 98%
“…Eldosoky (2012) showed that young mothers, employed mothers, educated mothers (with university degrees) and mothers with high socio-economic status had higher knowledge and more positive attitudes compared to others. In addition, Tomruk et al showed that studying at university results in an increase in mothers' knowledge about home injuries (Tomruk, Soysal, Gunay, & Cimrin, 2007). Thein et al (2005) emphasised the low level of mothers' knowledge about home safety and prevention of home accidents and showed that an increase in educational status results in an increase in mothers' knowledge.…”
Section: Discussionmentioning
confidence: 98%
“…These results are similar to those of Tomruk et al in Turkey, who found that bystanders in emergency situations answered an Willing to undergo training on first aid. 1450 100.0 average of 44.8% of questions correctly ( [22]. This low score contributes to the burden of the problem, as the first action taken for management of an injury decides its future course and complication rates [6].…”
Section: Discussionmentioning
confidence: 99%
“…Thein et al reported that the higher the education of the mother, the more likely she was to possess the correct knowledge and practice on childhood injuries [9]. Tomruk et al concluded that those who had graduated from a university, were health care personnel, had taken a first aid course or had a first aid certificate had better knowledge [22]. One explanation of our results is that almost all younger mothers in this sample had completed university education, and may therefore have more health awareness and more motivation to join training courses or read texts about baby and child care including first aid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First aid is the provision of initial care for an illness or injury, usually by a non-expert but trained person, until medical treatment can be accessed. Provision of immediate first aid to patients who require emergency care can make a big difference to the outcome [Tomruk et al, 2007], as the first action taken for management of injuries and common illness decides the future course of disease and complication rates [Hecht , 2012]. Parents' knowledge and practice about first aid is especially important in injury care for children, as many adverse consequences of injuries can be averted if parents know what actions to take, (Ibrahim , 1991).…”
Section: Introductionmentioning
confidence: 99%